Concurrent Hepatic and Pulmonary Fasciolosis in a White Fulani Cow: A Case Report Highlighting Food Safety and Economic Implications (Sahel Journal of Life Sciences FUDMA, 2025)
Fasciolosis, caused by liver flukes of the genus Fasciola, remains a globally significant parasitic disease of ruminants, with annual economic losses exceeding US$3.2 billion due to decreased productivity and organ condemnation. We report a rare case of concurrent hepatic and pulmonary fasciolosis in a 400 kg White Fulani cow that resulted in condemnation of both the liver and lungs at postmortem inspection. Clinically, the animal presented with respiratory distress, jaundice, dehydration, weight loss, and emaciation. Fecal examination revealed operculated Fasciola eggs, while necropsy demonstrated severe hepatic fibrosis, necrotic tracts, pipe-stem lesions, and adult flukes, alongside pulmonary congestion, necrotic foci, and adhesions consistent with ectopic migration. This case emphasizes the parasitological and pathological significance of fasciolosis, its contribution to economic losses in the cattle industry, and the zoonotic risk to humans. The report highlights the necessity of integrated control strategies, including regular anthelmintic treatment, improved animal husbandry, snail control, and strengthened abattoir surveillance to safeguard both livestock health and food safety.